Immune-based therapies in acute leukemia - Witkowski, Matthew T. (Trends Cancer, 2019)
Treatment resistance remains a leading cause of acute leukemia -related deaths. Thus, there is an unmet need to develop novel approaches to improve outcome. New immune-based therapies with chimeric antigen receptor (CAR) T cells, bi-specific T cell engagers (BiTEs) and immune checkpoint blockers (ICB) emerged as effective treatment options for chemo-resistant B-cell acute lymphoblastic leukemia (B-ALL) and acute myeloid leukemia (AML). However, many patients show resistance to these immune-based approaches. This review describes critical lessons learned from immune-based approaches targeting high-risk B-ALL and AML, such as the leukemia-intrinsic (e.g. target antigen loss, tumor heterogeneity) and extrinsic (e.g. immunosuppressive microenvironment) mechanisms driving treatment resistance, and discusses alternate approaches aimed at enhancing the effectiveness of these immune-based treatment regimens.